A Case of third molar autotransplantation into first molar recipient site with periapical granuloma - Yuni Rahmawati; Maria Goreti Widiastuti; Poerwati Soetji Rahajoe (MKGK (Majalah Kedokteran Gigi Klinik) (Clinical Dental Journal) UGM, 2017)
Autotransplantation of molar is a potential treatment option to restore perfect occlusion and to improve mastication following a substantial loss of molars. A succesful transplantation depends on the general patient condition, the donor tooth, and the recipient site. An ideal recipient site should have sufficient alveolar bone support, periodontal, and tissue and absence of chronic inflamation. We reported a case of third molar autotransplantation to first molar with periapical granuloma as recipient site with one year follow-up. Autotransplantation process started with an adequate curettage of the recipient site immediately, followed by atraumatic donor tooth extraction. The result of clinical and radiological examination showed no pain, no tooth mobility, and no inflammation at periapical first molar region. Periapical granuloma at the recipient site is not an absolute contraindication of autotransplantation. Extra-alveolar period and atraumatic extraction of the donor tooth during autotransplantation affected the condition of periodontal ligament